Analisa Hasil Simulasi Antena Mikrostrip Yagi Pada Frekuensi Kerja 1,9-2,1 GHZ Menggunakan Aplikasi Ansoft HSFF Versi 13.0 - Rendra Widianto; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Microstrip antenna as a communcation device has small dimension with good receiving signal ability, this microstrip antenna is a technology that can be used on a wireless network application with high rate data speeds. This microstrip antennas are small, designed in such a way that can be used daily without causing bad image effects for user apperance. antenna yagi microstrip device can be implemented in various fields such as industry, science and medical. The result of the antenna design is carried out by simulation process using applications. The target results from the antenna are: frequency 2.0 GHz, return loss ≤ -10 dB, dan VSWR ≤ 1.9.Keyword: microstrip antenna, Gain, radiation pattern, return loss, VSWR